Application of an advanced soil constitutive model to the study of railway vibrations in tunnels through 2D numerical models: a real case in Madrid (Spain) - Fernández Ruiz, Jesús; Medina Rodríguez, Luis (Revista de la Construcción. Journal of Construction, 2015)
In the last few years, different numerical models for the study of railway vibrations in tunnels have been developed. Virtually all of them assume an elastic and linear behaviour of the soil. In this article the influence of soil constitutive model is investigated, comparing an “advanced” model of the soil called Hardening Soil model with small-strain stiffness (HSsmall) and the Mohr-Coulomb (MC) model. Moreover, the influence of soil stiffness has been studied when this is considered in the range of small strains (E50) or in the range of very small strains (E0). These models have been applied to a real case through a 2D finite element model formulated in the time domain, where it is concluded that both soil stiffness and the amplitude of the maximum tangential strain are the most important geotechnical parameters when estimating the deformational parameters and the constitutive models of the soil most adequate for the study of railway vibrations in tunnels.